Effects of dietary glucosamine sulfate sodium on early laying performance and eggshell quality of laying hens - Ying Wang; Yanhua Huang; Panhong Zhou; Shengtao Lu; Jiale Lin; Guanglin Wen; Xiaoli Shi; Yuming Guo (Poultry Science, 2024)
ABSTRACT: This study was conducted to determine the influence of dietary glucosamine sulfate sodium (GSS) on laying performance, blood profiles, eggshell and inner quality of eggs and relative expression of the genes related to eggshell in laying hens at early stage. A total of 640 twenty-weeks-old Lohmann laying hens were randomly allotted to 4 treatments with 10 replicates of 16 hens each. The experiment lasted for 8 wk, and dietary treatments were: 1) CON, basal diet; 2) G1, CON + 0.2% GSS; 3) G2, CON + 0.4% GSS; 4) G3, CON + 0.6% GSS. The inclusion of GSS increased average daily feed intake, laying rate, and egg mass (P < 0.05) linearly during wk 21 to 25, 25 to 29, and 21 to 29, egg weight during wk 21 to 25 and 25 to 29, and improved (P < 0.05) feed conversion ratio linearly during wk 21 to 25. The supplementation of GSS increased (P < 0.05) albumen height quadratically, Haugh unit, calcium content, calcium mass, phosphorus content and phosphorus mass linearly at the end of 25th and 29th wk. At the end of 29th wk, the eggshell strength, eggshell weight, eggshell ratio, and eggshell thickness were increased (P < 0.05) linearly in GSS treatments compared with CON. The addition of GSS increased (P < 0.05) serum calcium, estrogen 2, and calcitonin, while decreased (P < 0.05) serum tartrate resistant acid phosphatase (TRAP), parathormone, IL-6 and prostaglandin E2 (PGE2) at the end of 29th wk. The inclusion of GSS increased (P < 0.05) the relative expression of ovocalyxin-32 and ovocalyxin-36 linearly at the end of 29th wk, and ovalbumin, osteopontin, calbindin 1, and ovocleidin-116 linearly at the end of 25th and 29th wk. Quadratic effects were observed (P < 0.05) in the laying rate during wk 21 to 25, serum TRAP and PGE2, the relative expression of ovocleidin-116 at the end of 29th wk. In summary, the inclusion of GSS up-regulated relative expression of osteopontin, ovocleidin-116, ovocalyxin-32 and ovocalyxin-36 in uterus, promoted the serum PGE2 and calcitonin, thus increased the calcium content of eggshell and finally enhanced eggshell quality.